Tinjauan Motivasi Kerja Karyawan Pada Hotel Arborbiz Makassar - Muhammad Arfah; Syafrimansyah Syafrimansyah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The research as aims to determine the work motivation of employees of the Arborbiz Makassar Hotel.The type of reseach used is descriptive qualitative, that is, the author describes the results of direct observtions and interviews with employees of the Arborbiz Makassar Hotel. The writing of this final draft is the results of research conducted from June to July 2022. The results showed that the work motivation of employees of the Arborbiz Makassar Hotel was perceived from several factors that influenced work motivation of employees, such as promotions, job performance, the job itself, rewards, responsibilities and recognition from superiors. These things have an increasing impact on work motivation for employees who work at the Hotel Arborbiz Makassar, thereby encouraging employees to work better and more effectively.